(3cdGe GdMbfs - (3LGdjfhSs
(3ChdgG (B:s
(3GdCUd ai ESJYeGd GdMbf cGf ef GdWHjYI HWGFQ cGf cKjQ GdCcd hcGf aVdGJg JMJbf acGf jCJi Edi GdHMQ ajedkG efbGQg eGA hjMbf Hg ajSJWdb HWfg s
(3BNQgG (B:s
(3PcQ COhjI eSJYedI ai GdMbf Je cdGe LGdjfhS ai GdMbf hddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3fSNI fbjSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/7) s
Keywords: (3GdadSaI hGdefWbs